Population Status and Habitat Preferences of Critically Endangered Dipterocarpus littoralis in West Nusakambangan, Indonesia - Robiansyah, Iyan; Davy, Anthony John (Makara Journal of Science, 2015)
The conservation of the endemic tree species Dipterocarpus littoralis (Bl.) Kurz. is hampered by the paucity of information on its population biology and ecology. Consequently, a targeted survey was carried out in the West Nusakambangan Nature Reserve to assess its population size and structure as well as habitat preferences. In total, 676 individuals of D. littoralis were located at 52 locations, with an extent of occurrence of 3.66 km2 and an area of occupancy of 1.71 km2. The population had an inverse-J-shaped distribution of diameter at breast height (DBH), with 63% of individuals in the 0-5 cm class and another 21% in the 5-10 cm class; only 11 (1.6%) mature individuals (DBH≥30) were found. D. littoralis was associated with steep, low, southwest-facing sites and sites that had high litter cover and thickness. Illegal logging and fuel-wood chopping were the main threats to D. littoralis and its habitat. In addition, an invasive shrub, Langkap (Arenga obtusifolia, Arecaceae), was a potential competitor with the seedlings throughout the reserve. In view of its endemism, narrow range and localized distribution, small population, environmental preferences, and the severe threats from anthropogenic activities and invasive species, D. littoralis appears to more than justify its conservation status of Critically Endangered.